Answer:
see explanation
Explanation:
let y = f(x) and rearrange making x the subject, that is
y =
← multiply both sides by (x + 1)
y(x + 1) = 2x - 3 ← distribute left side
xy + y = 2x - 3 ( subtract y from both sides )
xy = 2x - 3 - y ( subtract 2x from both sides )
xy - 2x = - 3 - y ← factor out x from each term on the left side
x(y - 2) = - 3 - y ← divide both sides by y - 2
x =
factor out - 1 on numerator and denominator
x =
![(-(3+y))/(-(2-y))](https://img.qammunity.org/2020/formulas/mathematics/high-school/5u1rveuj0n5iav9cpuavjccy5aju0c3yru.png)
Change y back into terms of x, thus
(x) =
=
![(x+3)/(2-x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/5jros46xblxarralt3drcwan8dtfod272j.png)